The microbe and the macropolicy - Rugalema, Gabriel (Technical Centre for Agricultural and Rural Cooperation, 2000)
In Africa, AIDS affects everyone in the community. When I was working on HIV/AIDS in Tanzania in 1999, I found myself talking to district administrators and farmers in terms of which households are afflicted, which households are affected and which...